Pengembangan Model Bimbingan Perkembangan terhadap Kecerdasan Spiritual Anak Melalui Pendidikan yang Mencerahkan - Elfiah, Rifda (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Entering the third millennium, the development of intelligence in humans at least there has been a spectacular change. When the first term of intelligence as though only monopolized sense or reason (intellectual), but a series of the recent discovery in the field of modern psychology, legend IQ as the sole parameter intelligence fell. Currently, it is believed that the intelligence turned out to be complex (compound), which is referred to as Gardner's multiple intelligences.               If during intelligence interpreted as if reason or logic, though now encroaching upon the emotional and spiritual. Goleman has popularized the emotional intelligence as breakthrough new ways to measure the extent of human intelligence in controlling emotions, bring a sense of empathy, understand the feelings of self and others, as well as how to control him. But people are still faced with the problem of "spiritual problem" that is causing people to not only stutter live in a more meaningful, but also their own dark about themselves.Is the development of guidance and counseling services, one of the methods to help children discover they're own potential hidden. But in reality, many teachers and parents have not been able to optimize the potential of the spirituality owned subsidiary. The impact, the development of spiritual intelligence of the child to be blocked and the hidden potency he already has too precipitate. Herein lies the urgency of integrated education and guidance in order to develop the spirituality aspect and potential of children so that it can be done on an ongoing basis.In this case, the guidance is directed to develop the whole child's development capabilities that include physical-motor abilities, intelligence, social, emotional, and spiritual. Guidance is done on children's education needs to be oriented in all aspects of child development, not only focused on one aspect of development alone. Delays in the development of one of the aspects that exist in children can inhibit the development of other aspects.